Investment policies in working capital and their impact on return and risk: an applied study in industrial sector companies for the period from 2006 to 2013 - Zahra Jarallah Hamo,; Hakem Mohsen Mohammed al - Rubaie, (Iraqi Journal for Administrative Sciences, 2024)
The purpose of this study is to analyze the relationship between the working capital investment policies and their effect on the return and risk by analyzingthe financial statements of the general budget and the income statement. The budget statements were used to the determining the adopted policy in current assets that forms the working capital which is of great importance to companies, administration especially business firms. A Sample of (15) Companies is chosen from (21) industrial sector companies for (8) years period from 2006-2013 Those companies are registed in the Iraqi stock exchange market (10) companies form the sample adopted a conservative Policy, ( 3) companies adopted a moderate Policy and two of them adopted a aggressive policy. A scientific statistical methodology was used to analyze the adopted policies . The main result of this study is that the working capital needs efficient administration which guarantee good depends for the analysis of these policiesWhere researcher to concluded to a group of most important conclusions the of the components of this variable So as to guarantee the good performance that effects companies return and profit.